LibQUAL+ in the UK and Ireland: three years' findings and experience - Lock, Selena A.; Town, J. Stephen (Cranfield University, 2011)
Presents an overview of the SCONUL LibQUAL+ participation, reports some of the overall results of the 2003-2005 SCONUL cohorts, and describes some feedback from participants and the lessons learnt from the process. The overall results for SCONUL in 2005 show that performance is a little above the minimum in Affect of Service and some problems of performance below the minimum in Information Control and Library as Place. There is a marked difference between the results for 2003 and the subsequent years, and one without obvious immediate explanation. Library as Place is the dimension which suggests more research is needed to understand the variation across the three years, and the particularly good results in the 2003 cohort. Consistently across all years the ability of libraries to deliver printed materials that staff and students require for their work, and the print or electronic periodical collection provision has scored below users' minimum expectations in the UK. For all major dimensions there was a decrease in perceptions in 2004. Library as Place is the only dimension to see a steady increase in users' expectations over the three years, Information Control expectations have remained fairly stable and Affect of Service has seen a decline in users' expectations. (Quotes from original text)
Keywords: Library management; Evaluation; Performance measures; Statistics; LIBQUAL+; Academic libraries; UK; Surveys; SCONUL